1999
DOI: 10.1021/la990459a
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Electrostatic Forces Using Higher Harmonics Tapping Mode Atomic Force Microscopy in Liquid

Abstract: A simple model of a damped, harmonic oscillator is used to describe the motion of an atomic force microscope cantilever tapping in fluid. By use of experimentally obtained parameters, excellent agreement is found between theory and experimental results. From the model we estimate that the force applied on the sample can range up to 100 nN, depending on the surface charge density. Detailed analysis of the cantilever deflection reveals subtle differences in the oscillatory motion, as a result of differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…dAFM methods for compositional contrast (elasticity or chemistry) in such soft materials are limited by the low cantilever quality factor in liquids [1][2][3][4][5]. In what follows, we demonstrate a significant improvement in this capability.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…dAFM methods for compositional contrast (elasticity or chemistry) in such soft materials are limited by the low cantilever quality factor in liquids [1][2][3][4][5]. In what follows, we demonstrate a significant improvement in this capability.…”
mentioning
confidence: 65%
“…The nonlinear tip-sample interaction in dAFM induces cantilever vibrations at higher harmonics of the drive frequency [1,[5][6][7][8][9][10] which can provide compositional contrast [1,[5][6][7]9,[11][12][13]. Under ambient or vacuum conditions, the higher harmonics are very small and need to be enhanced using special cantilevers [12] or bimodal excitation [14].…”
mentioning
confidence: 99%
“…It has been shown for AFM cantilevers that the higher harmonics of the fundamental mode of oscillation are often excited and this can be used to gain useful information about the sample. [25][26][27][28][29] The higher harmonics could be included in the analysis to yield a more accurate description of the dynamics and therefore an improvement in Eq. ͑8͒.…”
Section: -2mentioning
confidence: 99%
“…The nonlinear interaction force is able to be decoded from the spectrum of the higher harmonics. 83,114,115,[119][120][121] It has been demonstrated that the amplitude of the higher harmonics decreases with the order increasing; hence, when the amplitude decreases to the decay length of the short-range forces, the higher force gradients can be linked to the higher harmonics spectrum, which will increase the spatial resolution as well. 122,123 However, the rapid decay of the amplitude of higher eigenmodes and harmonics are often beneath the background noise, causing the information related to the material properties to stay hidden.…”
Section: The Physical Meanings Of Multifrequency Excitations and Analmentioning
confidence: 99%